An exploratory qualitative study of caregivers' knowledge, perceptions and practices related to hospital hygiene in rural Niger - Caroline Marquer; Ousmane Guindo; Issa Mahamadou; Elodie Job; Susan M. Rattigan; Céline Langendorf; Rebecca F. Grais; Sheila Isanaka (Elsevier, 2021)
S U M M A R Y: Background: The risk of healthcare-associated infections is exacerbated by poor hygiene practices in health care facilities and can contribute to increased patient morbidity and mortality. In low-income settings, caregivers play a key role in maintaining proper hygiene during inpatient stays. We aimed to explore caregivers' knowledge, perceptions and practices related to hospital hygiene in a rural, sub-Saharan African setting. Methods: We conducted an exploratory qualitative study among caregivers of children admitted to an inpatient therapeutic feeding center in Madarounfa, Niger. Individual interviews with 28 caregivers of hospitalized children were conducted to explore their knowledge, perceptions and practices of hygiene in the health facility. Findings: Caregivers described a broad understanding of hygiene and reported knowledge of its importance in the hospital, particularly to prevent disease transmission and protect child health. Hygiene was perceived as a collective rather than individual responsibility. Caregivers reported on the poor hygiene practice of others and cited a lack of space and hygiene materials as barriers to correct hygiene practice. Caregivers described educational sessions and informal sharing with other caregivers as tools to gain knowledge and improve practice. Conclusion: This exploratory study is unique in describing the perspective of caregivers in a low-resource hospital setting, a group often underrepresented when designing health interventions to improve hospital hygiene. Our findings suggest a strong knowledge of hospital hygiene among caregivers in this setting, with positive perception of its importance in health promotion. Poor individual practice was reported but may be improved through additional education and provision of hygiene materials.